Strategi Reaktivasi Desa Wisata Panundaan Berbasis Community Based Tourism (CBT) untuk Penguatan Pariwisata Berkelanjutan - Annisa Lazuardina; Evi Novianti; Raden Rizki Muttaqien; Sheila Nurhaliza; Shalma Aulia Wulandari; Irene Putri Simamora (JURNAL AKADEMISI VOKASI, 2025)
This study aims to evaluate the tourism potential and community-based management challenges in Panundaan Tourism Village, Bandung Regency. The village holds various local assets, including educational agriculture, Etawa goat farming, Sundanese cultural heritage, a community-based waste bank, and agro-processed MSMEs. Using a qualitative descriptive approach, data were collected through participatory observation, semi-structured interviews, and document analysis. The findings indicate that while Panundaan Village possesses diverse tourism attractions, its development is hindered by low community participation, inactive tourism awareness groups (Pokdarwis), and limited administrative capacity. Community empowerment has not been fully integrated into tourism governance, resulting in suboptimal utilization of local resources. The study proposes strategic work programs focusing on human resource development, institutional strengthening, infrastructure enhancement, and digital tourism promotion. These strategies aim to foster sustainable, inclusive tourism based on the principles of Community-Based Tourism (CBT). The implications highlight the importance of stakeholder collaboration in enhancing the village’s competitiveness as a sustainable tourism destination.